From Action Learning To The Teaching Organization - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
This paper expounds action learning for effective change leadership development using the learning-teaching helix as a paradigmftw introspection. Which consists of five phases â Awareness phase (ascertain 'our strengths and weaknesses), Alignment phase (identift .1.0111 core competence), Action phaselsynthesize Your work, business and management skills), Adoption phase (becoming a leader) cmd Assurance phase (excel as an educator cum coach). In addition, to succeed, the individual has to plan, strategize, prioritize and integrate. As a holistic manager the individual needs to think, feel and do to evolve from continuous action learning to the cycle of teaching for continuous innovation in organizational performance capabilities.